2015
DOI: 10.1007/jhep02(2015)146
|View full text |Cite
|
Sign up to set email alerts
|

Giant tachyons in the landscape

Abstract: Abstract:We study the dynamics of localized and fully backreacting anti-D3 branes at the tip of the Klebanov-Strassler geometry. We use a non-supersymmetric version of the Polchinski-Strassler analysis to compute the potential for anti-D3 branes to polarize into all kinds of five-brane shells in all possible directions. We find that generically there is a direction along which the brane-brane interaction is repulsive, which implies that anti-D3 branes are tachyonic. Hence, even though anti-D3 branes can polari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 57 publications
6
124
1
Order By: Relevance
“…Of course, supersymmetry must be broken anyway, but it would be preferable to break it spontaneously rather than explicitly. Attempts to realize the KKLT uplifting in supergravity or string theory have failed so far (Bena et al, 2012(Bena et al, , 2013, but opinions differ on the implications of that result. There exist several alternatives to D3-brane uplifting (see e.g.…”
Section: Existence Of De Sitter Vacuamentioning
confidence: 99%
“…Of course, supersymmetry must be broken anyway, but it would be preferable to break it spontaneously rather than explicitly. Attempts to realize the KKLT uplifting in supergravity or string theory have failed so far (Bena et al, 2012(Bena et al, , 2013, but opinions differ on the implications of that result. There exist several alternatives to D3-brane uplifting (see e.g.…”
Section: Existence Of De Sitter Vacuamentioning
confidence: 99%
“…From the analogy with the AdS 7 solution we expect that the singularity gets resolved by polarising the p-brane into a spherical (p + 2)-brane wrapping a finite size 2-sphere inside the S 3 . The non-compact "anti-brane" solutions, that have a flat worldvolume Mink p+1 instead of AdS p+1 cannot be stabilised at finite radius and hence the singularity cannot be resolved that way [46][47][48][49].…”
Section: Jhep03(2015)161mentioning
confidence: 99%
“…Analogous, albeit supersymmetric, examples of this type are known to give rise to singularities that are resolved by letting the 3-branes polarise to (p, q)-5 branes [24]. For smeared D3-branes there is a growing body of work that indicates that certain expected polarisation channels seem absent [25][26][27] and others lead to tachyonic modes [28][29][30][31]. Analogous results for fully localized branes are not as strong and a recent paper found that polarised D3-branes can be made regular by fixing boundary values of some fields [32].…”
Section: Jhep03(2017)141 2 Backreaction Effects and Instabilitiesmentioning
confidence: 99%